Tungsten disulfide based wearable antenna in terahertz band for sixth generation applications - Avijit Roy; Md. Razim Bhuiyan; Md. Ariful Islam; Pahil Saha; Sumit Hassan Eshan; Raja Rashidul Hasan; Rinku Basak (Universitas Ahmad Dahlan, 2024)
Wireless communication networks could become quicker and more dependable as sixth generation (6G) antennas develop. One difficult development in the field of wearable technology is wearable textile antennas. Wearable textile antennas require flexible building materials, primarily textiles with planar structures. This study will concentrate on the design and specification of microstrip rectangular patch antennas that use a variety of fabrics as the substrate, such as lycra, polyester, and washed cotton. Using two-dimensional (2D) materials in the terahertz (THz) range, the study presented here will help in the construction of appropriate wearable antennas. This work may significantly improve materials science and engineering by investigating and using 2D materials, such as tungsten disulfide, in antenna design. The suggested antennas’resonance frequencies are 1.1254 THz for polyester substrates, 4.4019 THz for washed cotton, and 2.9861 THz for lycra substrates. For substrate materials such as lycra, polyester, and washed cotton, the measured return loss was -44.92 dB, -38.17 dB, and -20.75 dB. This study could lead to the creation of new technologies and materials, such tungsten disulfide, which would have far-reaching uses outside of wearable electronics and provide significant advantages for society.